Studies on the Odonata and Trichoptera of high-elevation lakes of northern Colorado and southern Wyoming - Al Mousa, Moh'd Anwar, author; Nachappa, Punya, advisor; Fairchild, Matthew, advisor; Boone, Randall, committee member (Colorado State University. Libraries, 2021)
Freshwater biodiversity loss is a major concern, and global warming is already causing a significant role in species extinctions. The main goal of this research was to provide a baseline for specific aquatic insect species distributions at high-elevation lentic habitats in Northcentral Colorado and Southern Wyoming. I provided occurrence records of the Hudsonian Emerald dragonfly (Somatochlora hudsonica, HED) in Northcentral Colorado and Southern Wyoming. The HED is the only Colorado dragonfly listed as threatened by the US Forest Service. It was ranked as critically imperiled in Colorado and vulnerable in Wyoming. I used Maxent (Maximum entropy), a machine learning program that uses species presence data and environmental variables to predict the potentially suitable habitat for species. Maxent was used to plot a map of the potentially suitable habitats of HED. Temperature seasonality, mean temperature of wettest quarter, precipitation of warmest quarter, precipitation of driest quarter, and precipitation seasonality were the key environmental factors for predicting the occurrence of HED in appropriate high-elevation lakes of Northcentral Colorado and Southern Wyoming with an accumulated contribution of 91%. Results of this study provided baseline data for the US Forest Service to assist to evaluate the conservation status of HED and potentially initiate protection plans in two national forests (The Arapaho & Roosevelt National Forest and the Medicine Bow & Routt National Forest) in Colorado and Wyoming. I report adult caddisflies from 136 montane and alpine lentic habitats, primarily lakes, of seven northern Colorado counties for the first time. My objective was to provide species records of adult and larval caddisflies from high-altitude lentic habitats that are not generally well sampled. These lakes may be potentially impacted by current and future global climate change scenarios. Field collection of adults and rearing of larvae were included with available unpublished and published records, resulting in 541 confirmed records of caddisfly species. Forty-nine species, representing 24% of all known Colorado caddisflies are documented. Seven families and 24 genera are represented. The Limnephilidae comprised 76% of the 49 recorded species. The other six families were usually represented by only one to four species. Distribution maps are presented for the six families and the most common limnephilid species. Montane and alpine lakes are vulnerable ecosystems likely to be impacted by climate change. Comprehensive faunal surveys are key to understanding long–term biodiversity changes and establishing conservation needs and priorities. In addition, species lists of taxa are important to monitor future faunal biodiversity changes.